2021
DOI: 10.1123/tsp.2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ Use of Motivational Interviewing in Sport: A Qualitative Enquiry

Abstract: This study explored the use of motivational interviewing (MI) in sport contexts by experts in that approach. Specifically, the purpose was to understand which aspects of the MI approach are deemed valuable for working in sport and to begin to understand how these aspects are best applied. Nine practitioners participated in semistructured interviews, and thematic analysis identified themes related to core and subcomponents of MI (e.g., relational spirit, technical microskills, applied tools, and the MI communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Providing ample emotional support could be improved by developing the coach-athlete relationship in order to help ease the power dynamics at play. Training in motivational interviewing, for example, could be an appropriate intervention to target relationship building and communication (Mack et al, 2021). While this would be a positive step, further avenues and layers of support should be available away from those stakeholders.…”
Section: Applied Implicationsmentioning
confidence: 99%
“…Providing ample emotional support could be improved by developing the coach-athlete relationship in order to help ease the power dynamics at play. Training in motivational interviewing, for example, could be an appropriate intervention to target relationship building and communication (Mack et al, 2021). While this would be a positive step, further avenues and layers of support should be available away from those stakeholders.…”
Section: Applied Implicationsmentioning
confidence: 99%
“…Crucially, the eighth stage discusses the importance of recognising when MI is not working with a given client, or is not the optimal approach for the presenting issue, and should be put aside in favour of an approach which may be more effective. These eight stages in learning MI may be of value in designing MI training curricula and ongoing support of the MI learning process, evidenced by a number of them repeatedly cited in a systematic review of studies reporting MI training for general health care practitioners (Söderlund, Madson, Rubak, & Nilsen, 2011), in addition to being described as essential by participants in study two of the current res earch project (Mack et al, 2021). Miller and Mount (2001) showed that one workshop on MI (15 hours contact time over two days) was enough to sustain significant practitioner MIconsistent behaviours at 4 month re-test, but this effect was not large enough to initiate significant change in client outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported in this chapter has been published: Mack, R.,Breckon, J., Butt, J., & Maynard, I. (2021).…”
mentioning
confidence: 99%